FAKTOR-FAKTOR YANG MEMPENGARUHI PERINGKAT OBLIGASI LEMBAGA KEUANGAN YANG TERDAFTAR DI BEI - Chelsy Felicia, Sufiyati (Fakultas Ekonomi, Universitas Tarumanagara, 2020)
The purpose of this study is to find out whether there is an effect of liquidity, leverage, profitability, activity and firm size on the bond ratings of financial institutions listed on the Indonesia Stock Exchange (IDX) for the 2015-2017 period. This study uses a purposive sampling method. The number of samples used in this study were as many as 114 samples. The results of this study show that liquidity has a significant negative effect on bond ratings, leverage has a significant negative effect on bond ratings, profitability has a significant positive effect on bond ratings, activity has no influence on bond ratings and firm size has a significant positive effect on bond ratings. The results also show that liquidity, leverage, profitability, activity and firm size together influence bond ratings.